P89 "Not only Carotid: two unusual cases of treatment of steno-obstructions. (29th August 2022) - Corraine, S; Ledda, V; Schirru, F; Erta, M; Ferrari, A; Fusaro, F; Comelli, S
Abstract : Introduction: The persistent primitive hypoglossal artery (PPHA) is the second most common fetal residue carotid-basilar anastomosis with an estimated incidence of 0.02÷0.30%. A case of an awake ischemic stroke from internal carotid stenosis and basilar tip obstruction and a case of internal carotid artery restenosis, both associated with persistent primitive hypoglossal artery, are reported and summarized in this abstract. Methods: Case 1: Female, 42-year-old, was hospitalized with wake-up stroke and rapid worsening of symptoms up to coma; MRI revelated cerebellar and occipital lesions in DWI and the MR-Angiography showed the obstruction of the basilar tip. The patient was taken to the Angio-suite to undergo an i.a. mechanical thrombolysis. Cerebral angiography revelated bilateral vertebral hypoplasia, thrombotic near occlusion in left ICA and ipsilateral PPHA. After basilar recanalization ICA thrombosis was treated deploying a self-expanding stent. The procedure showed a complete recovery of the vessel lumen. Case 2: Female, 84-year old, was hospitalized with asymptomatic restenosis of the left internal carotid after CEA, and right ICA stenosis; Carotid duplex ultrasonography showed ulcerated plaque causing 65% stenosis (NASCET criteria). During endovascular treatment, cerebral angiography revealed a left PPHA. CAS was performed using a distal protection device in ICA; at final check the complete regain of the vessel lumen was observed and no complications were reported. Conclusions: The persistence of fetal anastomosis between carotid and basilar artery would represent a posterior cerebral circulation risk for ischemia and embolic infarction; in these cases the menagement of carotid steno-obstructions is challenging and requires special considerations. References: Jin X, Sun L, Feng Z, Li X, et. al. Persistent Hypoglossal Artery as a Potential Risk Factor for Simultaneous Carotid and Vertebrobasilar Infarcts. Front Neurol. 2018 Oct 11;9:837. Burgard M, Psathas E, Mordasini P, et. al. Symptomatic Internal Carotid Artery Stenosis in the Presence of a Persistent Primary Hypoglossal Artery. Vascular. 2021 Aug;29 (4):543–549. George Y. Luh, Bruce L. Dean, et. al. the Persistent Fetal Carotid-vertebrobasilar Anastomoses. AJR 1999 May, 172;1427–1432 Seeap, Baranoskijf, Floresbc, et.al. Republished: Basilar Stroke from a Persistent Hypoglossal Arteryjournal of Neurointerventional Surgery2017 Do you have any conflict of interest to declare? : No